EFFECTIVE MANAGEMENT OF FUNDRAISING STRATEGIES: DIRECT AND INDIRECT METHODS BY BAITUL MAAL PONDOK DIGITAL - Andrilolo Andrilolo; Mohammad Mas’ud Jauhari; Johari bin Abdullah (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
Fundraising is a method that is usually carried out by social institutions. Fundraising is very important in social institutions because activities in social institutions are related to humanity which requires funds from donors to be distributed to the community. This research aims to find out what fundraising strategies are carried out by Baitul Maal Pondok Digital (BPD) so that humanitarian programs can run. The type of research carried out was field research taking the research location at Baitul Maal Pondok Digital (BPD) and using a descriptive qualitative approach. Data collection by means of interviews, observation and documentation. The aim of this research is to analyze in depth the fundraising strategy using direct and indirect Baitul Maal Pondok Digital (BPD) Kubu Raya Regency methods. This research is descriptive research with a qualitative approach. From the results of this research, namely the formulation of strategies using direct and indirect methods in terms of content and implementation time for the strategy formulation that has been carried out, it can be concluded that the fundraising carried out by Baitul Maal Pondok Digital (BPD) is in accordance with the fundraising objectives.